The effects of acupressure on pain, anxiety and vital signs in patients undergoing coronary angiography: A randomized and sham-controlled trial - Bal, Selda Kartal; Gun, Meral (Elsevier Science Inc, 2024)
Aim: This randomised sham-controlled trial aimed to analyse the effects of acupressure on pain, anxiety, and vital signs in patients who underwent coronary angiography. Materials and methods: After undergoing coronary angiography, 105 patients were randomised into acupressure (n = 35), sham acupressure (n = 35), and control groups (n = 35). Patients in the acupressure group received acupressure on the heart meridian 7 (HT7), large intestine meridian 4 (LI4), and pericardium meridian (PC6) acupoints 30 min after admission to the clinic, for a period of 16 min, whereas those in the sham group received acupressure on locations 1-1.5 cm away from these points. The control group received standard treatment. The patient information form, Spielberger's state anxiety inventory, visual analogue scale, and vital signs follow-up form were used for data collection. Findings: Consecutive measurements revealed that anxiety levels in the acupressure group were lower than that in the sham and control groups (p < 0.05). In addition, compared to the sham and control groups, the pain scores in the acupressure group decreased significantly after acupressure (p < 0.01). Although there was no significant difference between the pain scores of the sham group before and after acupressure intervention (p > 0.05), the scores of the control group increased significantly over time (p < 0.01). Finally, the vital signs decreased significantly in the acupressure and sham groups after intervention (p < 0.01), but increased significantly in the control group (p < 0.01). Conclusion: The findings of this trial indicated that acupressure is an effective method for reducing anxiety, pain, and vital signs.
Keywords: Acupressure; Coronary angiography; Pain; Anxiety; Vital signs